Dialogue and Intercultural Communication. Excuses to Think on Subject-Subject Relationship in Human Communication - Romeu Aldaya, Vivian (Universidad de Chile. Instituto de la Comunicación e Imagen, 2010)
The objective of this work is to try to recentrar the intention of the human communication in the original relation subject-subject, relation that is relegated mainly of the present studies of the communication. The relation subject-subject occupies a central space in the interpersonal level of the intercultural comunicativas relations, aspect little studied also by this sphere of the communication. By means of the reflection around the nature of the intercultural communication, its theoretical, methodologic and ethical challenge s we will analytically approach the concept of dialogue and its paper in the re-centramiento of the relation subject-subject in the human communication.